2017
DOI: 10.1186/s12913-017-2496-5
|View full text |Cite
|
Sign up to set email alerts
|

A network perspective on patient experiences and health status: the Medical Expenditure Panel Survey 2004 to 2011

Abstract: BackgroundThere is a growing emphasis on the need to engage patients in order to improve the quality of health care and improve health outcomes. However, we are still lacking a comprehensive understanding on how different measures of patient experiences interact with one another or relate to health status. This study takes a network perspective to 1) study the associations between patient characteristics and patient experience in health care and 2) identify factors that could be prioritized to improve health s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Study sample sizes were large and varied from 347 patients to 1 322 290 patients in respective studies. Researchers in most studies reported (8,18 33) statistically significant results in at least one of the study’s patient experience outcome measures. Fourteen of the study’s (20,22 29,31 35) authors used comparison groups as a methodological design to measure patient experience from multiple health-care perspectives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study sample sizes were large and varied from 347 patients to 1 322 290 patients in respective studies. Researchers in most studies reported (8,18 33) statistically significant results in at least one of the study’s patient experience outcome measures. Fourteen of the study’s (20,22 29,31 35) authors used comparison groups as a methodological design to measure patient experience from multiple health-care perspectives.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen of the study’s (20,22 29,31 35) authors used comparison groups as a methodological design to measure patient experience from multiple health-care perspectives. Several teams of researchers (21,32,35) used data from large Medicare databases to conduct their studies. Researchers used the subjective data from CG-CAHPS surveys to analyze the association of patients’ characteristics and patients’ reported experience in health care (36), health-care utilization (35), and a comprehensive primary care initiative (32).…”
Section: Resultsmentioning
confidence: 99%
“…If two variables were related only because they had the same parent variable, they were interpreted as conditionally independent in Bayesian network modeling. [ 13 , 19 , 21 ] Bayesian network modeling could be applied to identify the parent variables and the strengths of the linkages to parent variables in terms of conditional probabilities. [ 13 , 19 , 21 ]…”
Section: Methodsmentioning
confidence: 99%
“…[ 22 ] Sometimes causal interpretation can be inferred from the arcs in the networks. [ 20 ] The Bayesian network had been used in many disciplines, ranging from health systems research,[ 21 ] medicine,[ 23 , 24 ] biology,[ 25 ] and sociology[ 26 ] to study the conditional dependencies between variables. The modeling process was shown in Fig 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation